Experimental characterisation of titanium nitride transmission lines for applications as kinetic inductance travelling wave parametric amplifiers - Longden, JC; Boussaha, F; Chaumont, C; Klimovich, N; Tan, B-K (International Symposium on Space Terahertz Technology, 2023)
Travelling wave parametric amplifiers (TWPAs) made from highly nonlinear reactive superconducting thin films have been demonstrated to be a potentially viable quantum-noiselimited amplifier technology for various fundamental physics platforms, including microwave/millimetre (mm)/sub-mm astronomy, dark matter search experiments, absolute neutrino mass determinations, and qubit readout platforms. To date, only a limited number of successful kinetic inductance (KI-)TWPA devices have been reported, with the majority of them fabricated from niobium titanium nitride (NbTiN) thin films; although in principle, any highly nonlinear low loss superconducting film can be used to construct a KITWPA. In this proceeding, we explore the suitability of using a different type of superconducting film, titanium nitride (TiN) for such application. We report on the detailed analysis of the nonlinear behaviour of TiN films to ascertain the film’s suitability for application as KITWPA. We experimentally characterised TiN transmission lines at cryogenic temperatures to compare the results predicted with electromagnetic simulations. This characterisation and analysis allows us to understand the fundamental physics governing the behaviour of the TiN films, their merits and limitations, and whether they are well suited for applications as KITWPAs.